Hamstring-to-quadriceps torque ratios of professional male soccer players: A systematic review - Baroni, B. M.; Ruas, C. V.; Ribeiro-Alvares, J. B.; Pinto, R. S. (The Journal of Strength and Conditioning Research, 2020)
The goal of this review was to determine the isokinetic hamstring-to-quadriceps (H/Q) torque ratios of professional male soccer players. Systematic searches were independently carried out by 2 researchers in 7 electronic databases. Only studies with teams from the first or second national leagues were included. From these studies, we extracted the players' H/Q conventional (concentric/concentric) and/or functional (eccentric/concentric) ratios. The initial search resulted in 2,128 articles that were filtered to 30 articles (1,727 players) meeting the inclusion criteria. The H/Q conventional ratio was assessed in 27 studies (1,274 players), whereas the H/Q functional ratio was assessed in 15 studies (1,082 players). The H/Q conventional ratio mean scores of professional male soccer players were close to 60% when tested at low to intermediate angular velocities (12°·s-1 = 52 ± 7%; 30°·s-1 = 52 ± 8%; 60°·s-1 = 65 ± 12%; 90°·s-1 = 57 ± 6%; 120°·s-1 = 65 ± 16%; 180°·s-1 = 67 ± 17%) and around 70-80% at fast angular velocities (240°·s-1 = 80 ± 40%; 300°·s-1 = 70 ± 15%; 360°·s-1 = 80 ± 13%). The H/Q functional ratio mean scores of professional male soccer players were close to 80% at 60°·s-1 (79 ± 19%), around 100-130% at intermediate to fast angular velocities (120°·s-1 = 127 ± 42%; 180°·s-1 = 96 ± 19%; 240°·s-1 = 109 ± 22%; 300°·s-1 = 123 ± 18%), and near or above 130% when angular testing velocities were mixed (eccentric hamstring < concentric quadriceps; 30/240°·s-1 = 132 ± 26%; 60/180°·s-1 = 129 ± 20%; 60/240°·s-1 = 153 ± 30%). In conclusion, considering the tested isokinetic angular velocity, professional male soccer players do not meet the traditional reference landmarks used to assess the strength balance between quadriceps and hamstring muscles (i.e., 60 and 100% for H/Q conventional and functional ratios, respectively), which supports a need for specific reference values according to the angular velocity selected for testing H/Q torque ratios.